Video Demonstrations of a Benzene Derivative Reaction from Its Optimized Intermediate Structure - Awal, Jumaidil; Martoprawiro, Muhamad Abdulkadir (Universitas Negeri Malang, 2023)
A number of researchers have performed studies on the application of chemical reaction visualization by means of computational chemistry techniques for the purpose of teaching and learning chemistry at secondary and higher education levels. However, on practical grounds, the presented approach thus far was generally unattainable for teachers due to the time-consuming process of finding the transition states. This research offers a less time-consuming computational chemistry technique for producing organic reaction-modelling videos upon which the students may sufficiently build their understanding of fundamental concepts of chemical reactions. The technique being proposed here consists of (1) intermediate structure modelling, (2) reactant-wise and product-wise optimizations of the intermediate structures without the search for transition states, and (3) visualizations of the optimized results. The application of this technique has managed to produce a video demonstration of an organic reaction of benzene derivatives that may serve as modelling videos in chemistry lessons at secondary education or undergraduate degree levels.REFERENCESBode, B. M., & Gordon, M. S. (1998). Macmolplt: A graphical user interface for GAMESS. Journal of Molecular Graphics and Modelling, 16(3), 133–138. https://doi.org/10.1016/S1093-3263(99)00002-9Carey, F. A. (2000). Organic chemistry (4th ed). McGraw-Hill.Cohlberg, J. A. (2021). Exploring Proteins and Nucleic Acids with Jmol. W. H. Freeman and Company. https://home.csulb.edu/ cohlberg/Jmolmanual.pdfCramer, C. J. (2004). Essentials of computational chemistry: Theories and models (2nd ed). Wiley.Hanwell, M. D., Curtis, D. E., Lonie, D. C., Vandermeersch, T., Zurek, E., & Hutchison, G. R. (2012). Avogadro: An advanced semantic chemical editor, visualization, and analysis platform. Journal of Cheminformatics, 4(1), 17. https://doi.org/10.1186/1758-2946-4-17Ikuo, A., Ikarashi, Y., Shishido, T., & Ogawa, H. (2006). User-Friendly CG Visualization with Animation of Chemical Reaction: Esterification of Acetic Acid and Ethyl Alcohol and Survey of Textbooks of High School Chemistry. Journal of Science Education Japan, 30(4), 210–215.Ikuo, A., Nagashima, H., Yoshinaga, Y., & Ogawa, H. (2009). Calculation of potential energy in the reaction of